Different Plasmodium falciparum clearance times in two Malian villages following artesunate monotherapy. (June 2020) - Kone, Aminatou; Sissoko, Sekou; Fofana, Bakary; Sangare, Cheick O.; Dembele, Demba; Haidara, Aboubecrine Sedhigh; Diallo, Nouhoum; Coulibaly, Aoua; Traore, Aliou; Toure, Sekou; Haidara, Kadidia; Sanogo, Kassim; et al.
Highlights: High prevalence of residual parasitemia at day 3 post-artesunate monotherapy treatment using qPCR while no parasites were detected by microscopy at the same timepoint. A longer parasite clearance time observed in a Malian village. Artesunate treatment is still efficacious on Plasmodium falciparum in Mali. Abstract: Background: Artemisinin resistance described as increased parasite clearance time (PCT) is rare in Africa. More sensitive methods such as qPCR might better characterize the clearance phenotype in sub-Saharan Africa. Methods: PCT is explored in Mali using light microscopy and qPCR after artesunate for uncomplicated malaria. In two villages, patients were followed for 28 days. Blood smears and spots were collected respectively for microscopy and qPCR. Parasitemia slope half-life was calculated after microscopy. Patient residual parasitemia were measured by qPCR. Results: Uncorrected adequate clinical and parasitological responses (ACPR) observed in Faladje and Bougoula-Hameau were 78% and 92%, respectively (p = 0.01). This reached 100% for both after molecular correction. Proportions of 24H microscopy positive patients in Faladje and Bougoula-Hameau were 97.2% and 72%, respectively (p < 0.0001). Slope half-life was 2.8 h in Faladje vs 2H in Bougoula-Hameau (p < 0.001) and Proportions of 72H patients with residual parasitemia were 68.5% and 40% in Faladje and Bougoula-Hameau, respectively (p = 0.003). The mean residual parasitemia was 2.9 in Faladje vs. 0.008 in Bougoula-Hameau (p = 0.002). Although artesunate is efficacious in Mali, the longer parasite clearance time with submicroscopic parasitemia observed may represent early signs of developing P. falciparum resistance to artemisinins.